Cultures of a human synovial cell line to evaluate platelet‐rich plasma and hyaluronic acid effects. (27th June 2018) - Olivotto, E.; Merli, G.; Assirelli, E.; Cavallo, C.; Belluzzi, E.; Ramonda, R.; Favero, M.; Filardo, G.; Roffi, A.; Kon, E.; Grigolo, B.
Abstract: Synovial inflammation plays an important role in osteoarthritis (OA) pathogenesis. Different biological compounds have been tested mainly on chondrocytes, to treat early stages of OA. However, because OA has been recently defined as "an organ" pathology, investigation on synoviocytes is also needed. Therefore, the aim of the present study was to validate a human fibroblast‐like synoviocytes cell line (K4IM) to test the effects of platelet‐rich plasma (PRP) and hyaluronan (HA) on anabolic and catabolic gene expression and on HA secretion from cell cultures. In order to determine the effect of PRP and HA, K4IM cells were maintained in culture with or without TNF‐α stimulation. In the presence of PRP, unstimulated K4IM cells presented the same expression of IL1B, IL6, CXCL8, VEGF, TIMP1, and hyaluronic synthase isoform HAS3 as primary human synoviocytes, while HA addition did not change their expression pattern, which was similar to control cells. Stimulated cells expressed significantly higher values of IL1B, CXCL8, and VEGF compared with unstimulated ones. PRP did not show any modification, except for VEGF, while HA addition modulated IL1B expression. PRP did not modulate HA release of both stimulated and unstimulated cells. Our study showed the possibility to use K4IM synoviocytes as an in vitro model to test biological compounds useful for the treatment of early OA. Primary cells reflect the phenotype of cells in vivo, but limited recovery from biopsies and restricted lifespan makes experimental manipulation challenging. Therefore, despite cell lines present some limitations, they could be used as an alternative for preliminary experiments.